Speech articulation assessment using dynamic magnetic resonance imaging techniques - S. R. Ventura (2011)
Magnetic Resonance Imaging (MRI) has been successfully applied on real-time analysis of the articulators during speech production along the whole vocal tract, with good signal-to-noise ratio and without ionizing effects. Because speech dynamic events need a minimal sampling rate, an improvement on the temporal resolution of MRI systems is demanded. Our aim is to describe a dynamic MRI technique to acquire and assess the main articulatory events during the production of some European Portuguese utterances. Hence, novel perceptions for dynamic MRI technique using a 3.0 Tesla System are presented in order to study the shape of the vocal tract during speech production.